Data on evaluation of proficiency for the US-CAB curriculum - Wan-Ching Lien; Shu-Hsien Hsu; Kah-Meng Chong; Shyh-Shyong Sim; Meng-Che Wu; Wei-Tien Chang; Cheng-Chung Fang; Matthew Huei-Ming Ma; Shyr-Chyr Chen; Wen-Jone Chen (Data in Brief, 2018)
Data presented in this article relates to the research article entitled “US-CAB protocol for ultrasonographic evaluation during cardiopulmonary resuscitation: validation and potential impact” (Lien et al., in press). The article provides data regarding proficiency of the 10 emergency residents attending the US-CAB curriculum. Assessments included immediate evaluation at the end of training and re-evaluation 6 months later. A written test, and the ultrasound image acquisition were required in the immediate evaluation The re-evaluation included the written test and performance on the same healthy volunteer.